A STUDY ON THE PREVALENCE OF ACUTE LEUKEMIA AMONG A GROUP OF IRAQI PATIENTS - Mohammad, Taghreid Kheder; Mahmood, Asmaa Hashem; Elew, Genan Fadel; Al-Khalidi, Saja Jehad (Al-Nahrain Journal of Science, 2018)
Many children under 15 years of age and many adults more than 15 years of age with acute leukemia registered and treated in Oncology Department attached to the Al-Yarmuk Teaching Hospital and Child Central Hospital in Baghdad were enrolled in this study, as regards to their general characteristics and the type of acute leukemia. For comparison purposes, one year was chosen (2006), which showed that, the incidence with acute lymphoblast leukemia in children was 72.5%, while the incidence with acute myelocytic leukemia in adults was 27.5%. During the year, 2006, male predominance was evident. The fraction of patients living in urban areas was more that those of rural regions.The symptoms of leukemia patients were headache, vomiting, anemia, and fever (38-38.5Cº) for more than 2 weeks, fever pallor, spleen or liver were moderately enlarged or hepatosplenomegaly; in addition to throat and mouth lesions. Most children and adults also had thrombocytopenia, leucopenia and high rate of erythrocyte sedimentation rate. The frequency and general characteristic of acute leukemia in this study were compared to these reported else where.